An RBC model with non-Ricardian households: Lessons for Bulgaria (1999-2018) - Aleksandar Vasilev (Journal of Economics and Development, 2020)
Purpose: We introduce non-Ricardian ("hand-to-mouth") myopic agents into an otherwise standard real-business-cycle (RBC) setup augmented with a detailed government sector.We investigate the quantitative importance of the presence of non-optimizing households for cyclical fluctuations in Bulgaria. Design Methodology/approach: We calibrate the RBC model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). Findings: We find that the inclusion of such non-Ricardian households improves model performance along several dimensions and generally provides a better match vis-a-vis data, as compared to the standard model populated with Ricardian agents only. Originality/value: This is a novel finding in the macroeconomic studies on Bulgaria using modern quantitative methods.
Keywords: E24; E32; 330; business cycles; non-Ricardian households; hand-to-mouth; myopic behavior; Bulgaria